2023
DOI: 10.1101/2023.09.30.560259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin 11 therapy causes acute heart failure and its use in patients should be reconsidered

Mark Sweeney,
Katie O’Fee,
Chelsie Villanueva-Hayes
et al.

Abstract: BackgroundInterleukin 11 (IL11) was initially thought important for platelet production, which led to recombinant IL11 being developed as a drug to treat thrombocytopenia. IL11 was later found to be redundant for haematopoiesis and its use in patients is associated with unexplained cardiac side effects. Here we identify previously unappreciated and direct cardiomyocyte toxicities associated with IL11 therapy.MethodsWe injected recombinant mouse lL11 (rmIL11) into mice and studied its molecular effects in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Recently, it was shown that IL-11 expression in murine cardiomyocytes was associated with up-regulation of cytokines, chemokines, complement factors and an increase in inflammatory cells [46]. The treatment with rmIL-11 in mice showed that activation of the inflammatory response in the heart is associated with activation of the STAT3 pathway [47]. However, further investigations are needed to elucidate these effects more clearly for a better understanding of the biological role of IL-11 in cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that IL-11 expression in murine cardiomyocytes was associated with up-regulation of cytokines, chemokines, complement factors and an increase in inflammatory cells [46]. The treatment with rmIL-11 in mice showed that activation of the inflammatory response in the heart is associated with activation of the STAT3 pathway [47]. However, further investigations are needed to elucidate these effects more clearly for a better understanding of the biological role of IL-11 in cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%